2022
DOI: 10.9734/ijtdh/2022/v43i1730658
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Comorbidities in Douala, Cameroon

Abstract: Aims: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) still negatively impacting the world. This study aimed at determining the prevalence of COVID-19 and comorbidities, associated factors, and evaluating the impact of these comorbidities on COVID-19 patients. Study Design: Cross-sectional hospital-based study. Place and Duration of Study: From January to March 2022, the present study was conducted at four health facilities in Douala town (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…First, the distribution of comorbidities in study populations is likely an important factor modulating SARS-CoV-2 infection risk. We reported that obesity, diabetes, and hypertension were predominant comorbidities, and this finding was also reported earlier ( Ebongue et al, 2022 ; Kojom Foko et al, 2021 ; Loteri et al, 2022 ). Likewise, high prevalence values of diabetes and hypertension were found in hospitalized COVID-19 patients living in Douala and Yaoundé ( Mbarga Fouda et al, 2021 ; Mekolo et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…First, the distribution of comorbidities in study populations is likely an important factor modulating SARS-CoV-2 infection risk. We reported that obesity, diabetes, and hypertension were predominant comorbidities, and this finding was also reported earlier ( Ebongue et al, 2022 ; Kojom Foko et al, 2021 ; Loteri et al, 2022 ). Likewise, high prevalence values of diabetes and hypertension were found in hospitalized COVID-19 patients living in Douala and Yaoundé ( Mbarga Fouda et al, 2021 ; Mekolo et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…The COVID-19 vaccination uptake was relatively low in the study, which is lower than that reported previously in Cameroon 24,25 and a global estimate of COVID-19 vaccination uptake rate reported by Zhang and colleagues 15 . Other studies reported higher vaccine uptake in specific groups such as elderly persons, college students and transborder populations [26][27][28] .…”
Section: Discussioncontrasting
confidence: 81%
“…The details of study sites, eligibility criteria, and procedures have been published elsewhere [ [20] , [21] , [22] ]. Briefly, 420 patients were recruited at seven health facilities in the town of Douala from January to September 2022.…”
Section: Methodsmentioning
confidence: 99%
“…After signing an informed consent form, individual interviews lasting approximately 25 min each were performed using a structured questionnaire to collect demographical, biological, anthropometric, behavioral, and clinical characteristics. Nasopharyngeal samples were collected for molecular detection of SARS–CoV–2 based on retrotranscriptase quantitative polymerase chain reaction (RT-qPCR) analysis of the RdRp, E, et N genes using a DaAnGene® kit (DaAn Gene Co., Ltd, Guangzhou, Guangdong, China) as published earlier [ 20 , 21 ]. Briefly, the RT-qPCR was performed on an on a QuantStudio™ 7 real time thermocycler (Applied Biosystems, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%